2015
DOI: 10.1111/sapm.12083
|View full text |Cite
|
Sign up to set email alerts
|

Reduction Methods and Chaos for Quadratic Systems of Differential Equations

Abstract: We consider systems of differential equations with quadratic nonlinearities having applications for biochemistry and population dynamics, which may have a large dimension n. Due to the complexity of these systems, reduction algorithms play a crucial role in study of their large time behavior. Our approach aims to reduce a large system to a smaller one consisting of m differential equations, where m << n. Under some restrictions (that allow us to separate slow and fast variables in the system) we obtain a new s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The key point (iii) allows us to exhibit the existence of chaotic dynamics. This is found in [8], where it is shown that all kinds of structurally stable dynamics can be generated by quadratic systems. Thus, all structurally stable dynamics can appear as a result of bifurcations.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The key point (iii) allows us to exhibit the existence of chaotic dynamics. This is found in [8], where it is shown that all kinds of structurally stable dynamics can be generated by quadratic systems. Thus, all structurally stable dynamics can appear as a result of bifurcations.…”
Section: Introductionmentioning
confidence: 92%
“…Proof. According to results [8] for any ǫ 1 > 0 we can construct ǫ 1 -realization of the field Q by semiflows defined by (6.119). Moreover, due to the previous lemma, for any ǫ 2 > 0 we can find ǫ 2 -realization of any system (6.119) by semiflows defined by (6.98).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…where EIE −1 is the Green's operator of the first order system. Now, the solution of the given IVP ( 4) is obtained by collecting the first n rows ofũ as in equation (5). The uniqueness of the solution follows from the fact that homogeneous IVP has the trivial solution.…”
Section: Semi-inhomogeneous Initial Value Problemsmentioning
confidence: 99%
“…al. [5] considered a large system of quadratic differential equations and presented a reduction algorithm to reduce the large system to smaller systems under some restrictions. Mukesh [6] presented a new technique to solve higher order ordinary differential equations using modified Adomian decomposition method.…”
Section: Introductionmentioning
confidence: 99%